Five Years Survival Of Common Childhood Cancers In Guilan, The North Province Of Iran During 2013-2018 (Journal of Pharmaceutical Negative Results, 2023)
Cancers are the second leading cause of death in children after accidents. There are several factors that affect the survival rate of cancer patients, and the sum of these factors causes a huge difference between the survival rate of patients in different geographical areas of the world. Determining the survival rate of cancers after diagnosis is one of the key studies needed to review educational protocols and prevention strategies. In this retrospective cohort study, which was conducted as a census, the survival status of all children aged 0-14 years with cancer in Guilan province in 2018-2013, which was registered in the format of the cancer registration software program and is currently at the disposal of the health department of the university was investigated. Life table analysis or Kaplan -Meier method, Log Rank test and was used to calculate survival or comparing the survival of groups. 31.2% of children had the result of treatment leading to death and 68.8% had recovery. By comparing the median survival time of children, it was found that there is no difference between boys and girls and it was found that there is no difference in terms of where children live. The lowest 5-year survival rate of malignancies in children with cancer, respectively. Taken together, diagnostic protocols and comprehensive plans should be made for the follow-up of children with central nervous system, bone and blood system and endothelial cancers, especially in children who were diagnosed 0-5 years old.